The Effect of Innovation Strategies on Business Performance of Pharmaceutical Companies: The Moderating Role of Financial Management and Intellectual Capital - Mostafa Moradi; Alireza Yektadoost; Shekoufeh Nikfar (Tehran University of Medical Sciences, 2018)
Background: Management science is seeking ways to realize organizational goals, strategies, and expectations, which are the criteria for a company's successful performance. One of the most important aspects of management in an organization is the evaluation and measurement of business performance. Measuring business performance is crucial and according to some experts, "you cannot manage what you do not measure". Having a systematic view of business performance in pharmaceutical companies is of great significance. Methods: According to the studies and interviews with pharmaceutical experts, we developed a conceptual model and examined the factors affecting pharmaceutical companies' innovative strategies. A descriptive method, specifically the Partial Least Squares Structural Equation Modeling (PLS-SEM) was adopted. The statistical population of the study consisted of pharmaceutical companies' experts selected by cluster sampling. Also, according to the Morgan Table, the number of statistical population and sample members were 70 and 59, respectively. Results: The obtained results indicated that the key processes and product innovative strategies improved business performance. Financial management, as the moderator variable, affected the relationship between product and process innovation and business performance improvement. Intellectual capital, as the other moderator variable, affected the relationship between product and process innovation and business performance improvement. Conclusion: The findings of this study showed that factors, like financial management, product innovation strategy, process innovation strategy, and intellectual capital development significantly affect business performance improvement. Generally, a review of previous literature showed that the present study confirms their results to some extent and by including some factors, which had not been considered before, it is a more novel comprehensive research on this issue.